Cultural Hybridity in the Korean Wave Phenomenon Message on the TikTok Account @Kpopchartofficial (An Ethnographic Study for the Internet by Christine Hine) - Cintana Dinda Arlita; Fahrianoor (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The account @kpopchartofficial began gaining public attention on Instagram in 2012 and started operating on TikTok around 2020, along with the increasing consumption of Korean popular culture content through short-video-based social media platforms. The account currently has more than 2.2 million followers, follows approximately 435 accounts, and has gained over 175 million likes. This study aims to analyze cultural hybridity in the messages of the Korean Wave phenomenon on the TikTok account @kpopchartofficial, examine the role of the account as a third space facilitating the hybridization process between Korean culture and Indonesian local culture, and explore how users interpret and negotiate the mixture of Korean and Indonesian local cultures within the messages shared on the account. This study employed a qualitative approach using Christine Hine’s ethnography for internet method. The data collection techniques included observation, documentation, literature study, and interviews. The data were analyzed qualitatively and interpretatively based on the ethnography for internet approach proposed by Christine Hine. The theories applied in this research include cultural hybridity theory, social construction theory, and symbolic interactionism theory. The findings reveal that cultural hybridity in the messages of the Korean Wave phenomenon on TikTok occurs through content adaptation, localization of meaning, and active audience participation. The forms of cultural hybridity identified include integrative, negotiative, and agonistic hybridity, reflecting the dynamic interaction between global and local cultures. The TikTok account @kpopchartofficial functions as a digital cultural space that mediates this process, where audiences actively interpret and negotiate meanings. Therefore, the Korean Wave on TikTok is not merely consumed, but also reconstructed by audiences within their local cultural context.